Matrix metalloproteinases and tissue inhibitors in multiple myeloma: promote or inhibit? - Li, Yan-Ying; Zhang, Liu-Yun; Xiang, Yun-Hui; Li, Dan; Zhang, Juan (Frontiers in Oncology, 2023)
Matrix metalloproteinases (MMPs) and tissue inhibitor of metalloproteinases (TIMPs) play a vital role in the pathogenesis of multiple myeloma (MM), especially for tumor invasion and osteolytic osteopathy. By breaking down extracellular matrix (ECM) components and releasing the proteins composing the ECM and growth factors, as well as their receptors, MMPs affect tissue integrity and promote cancer cell invasion and metastasis. A vital pathophysiological characteristic of MM is the progress of osteolytic lesions, which are brought on by interactions between myeloma cells and the bone marrow microenvironment. MMPs, certainly, are one of the fundamental causes of myeloma bone disease due to their ability to degrade various types of collagens. TIMPs, as important regulators of MMP hydrolysis or activation, also participate in the occurrence and evolution of MM and the formation of bone disease. This review focuses on the role of MMP-1, MMP-2, MMP-7, MMP-9, MMP-13, MMP-14, and MMP-15 and the four types of TIMPs in the invasion of myeloma cells, angiogenesis, osteolytic osteopathy, to offer some novel perspectives on the clinical diagnostics and therapeutics of MM.